The relationship between self-efficacy and anxiety levels in elderly people with a history of hypertension in private elderly homes in Semarang city - Dwi, Selvi; Hartati, Elis (Universitas 'Aisyiyah Yogyakarta, 2025)
Hypertension is a condition when an individual has blood pressure of 140/90 mmHg or more. Physiological and psychological changes during the aging process cause the elderly to tend to experience hypertension. Hypertension not only affects physical conditions but also affects the psychological condition of the elderly, namely it can cause anxiety. One of the factors that affects anxiety is self-efficacy . Improving self-efficacy is crucial for enhancing the elderly’s quality of life. This study aims to determine the relationship between self-efficacy and anxiety levels in the elderly with a history of hypertension in private elderly homes in Semarang City. This study uses a non-experimental quantitative method with a correlational design. Sampling with a purposive sampling technique obtained 45 respondents, and the correlation test used the Pearson Product Moment test. The results of the anxiety level in the non-anxious category were 19 respondents (42.2%), and the elderly with high self-efficacy were 41 respondents (91.1%). The results of the correlation test obtained a significant value of 0.000, meaning 0.000<0.005. It can be concluded that there is a relationship between self-efficacy and anxiety levels. The suggestions in this study are expected to provide additional information that self-efficacy is important for reducing anxiety levels.